2010
DOI: 10.1002/btpr.398
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses to sodium chloride‐induced osmotic stress: A study of industrial fed‐batch CHO cell cultures

Abstract: The rapidly expanding market for monoclonal antibody and Fc-fusion-protein therapeutics has increased interest in improving the productivity of mammalian cell lines, both to alleviate capacity limitations and control the cost of goods. In this study, we evaluated the responses of an industrial CHO cell line producing an Fc-fusion-protein to hyperosmotic stress, a well-known productivity enhancer, and compared them with our previous studies of murine hybridomas (Shen and Sharfstein, Biotechnol Bioeng. 2006;93:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 47 publications
10
35
1
Order By: Relevance
“…cDNAs were prepared from mRNAs extracted from YB2/0 cells expressing IgG1 B that were sampled on days 6, 9, 11, and 12 during serum-free 1-L fed-batch culture in hypoosmotic (250 mOsm/kg) and hyperosmotic (410 mOsm/kg) media. Microarray analyses indicated that hypoosmotic conditions led to the downregulation of glycolysis gene expression, particularly pyruvate kinase and aldolase (data not shown), which is in agreement with the proteomic and transcriptomic analyses of the effects of osmotic stress on CHO and hybridoma (Shen and Sharfstein 2006;Shen et al 2010). Next, we used semi-quantitative RT-PCR to evaluate gene expression under hypoosmotic versus hyperosmotic conditions and observed three marked responses (Table 3).…”
Section: Rt-pcr Analysis Of Cultured Yb2/0 Cells In Bioreactorssupporting
confidence: 79%
“…cDNAs were prepared from mRNAs extracted from YB2/0 cells expressing IgG1 B that were sampled on days 6, 9, 11, and 12 during serum-free 1-L fed-batch culture in hypoosmotic (250 mOsm/kg) and hyperosmotic (410 mOsm/kg) media. Microarray analyses indicated that hypoosmotic conditions led to the downregulation of glycolysis gene expression, particularly pyruvate kinase and aldolase (data not shown), which is in agreement with the proteomic and transcriptomic analyses of the effects of osmotic stress on CHO and hybridoma (Shen and Sharfstein 2006;Shen et al 2010). Next, we used semi-quantitative RT-PCR to evaluate gene expression under hypoosmotic versus hyperosmotic conditions and observed three marked responses (Table 3).…”
Section: Rt-pcr Analysis Of Cultured Yb2/0 Cells In Bioreactorssupporting
confidence: 79%
“…Mitochondrial signaling was also heavily implicated in this study although there was no evidence of ER stress mediated apoptosis (Wong et al, 2006). Discrepancies in the stress responses between hamster and murine cell lines have also been seen in other studies in spite of a high level of sequence similarity (Shen et al, 2010) highlighting the importance of having a fuller understanding of the signaling mechanisms in a particular line, or for a particular set of conditions before embarking on process optimization and cell engineering experiments.…”
Section: Discussionmentioning
confidence: 73%
“…Increasingly, efforts have been made to probe transcriptomic and proteomic alterations between cells of different productivities (Charaniya et al, 2009;Khoo et al, 2007;Seth et al, 2007;Smales et al, 2004), culture conditions (Krampe et al, 2008;Shen et al, 2010;Swiderek and Al-Rubeai, 2007) or cells treated with chemical agents (Kantardjieff et al, 2010). Indeed, ''omic'' data available for mammalian cells have so far mainly been obtained in conventional batch/fed-batch shaker or bioreactor cultures.…”
Section: Introductionmentioning
confidence: 99%